Use of spatial communication in aphasia - Johnson, S.; Cocks, Naomi; Dipper, L. (Informa Healthcare, 2013)
Background: Spatial communication consists of both verbal spatial language and gesture. There has been minimal research investigating the use of spatial communication, and even less focussing on people with aphasia. Aims: The aims of this exploratory study were to describe the frequency and variability of spatial language and gesture use by three participants with aphasia in comparison to nine control participants. This included: 1) frequency of gestures; 2) types of gesture; 3) number of spatial descriptions described by gestures but no language; and 4) frequency and variety of locative prepositional, verb, and noun phrases. Methods & Procedures: Each participant was videoed undertaking 11 spatial communication tasks: four description tasks, and seven tasks involving directing the researcher in the placement of objects or pictures. Gestures and language produced were transcribed and analysed. Outcomes & Results: Participants with aphasia used significantly more gesture. Participants with aphasia also used more gesture without spoken phrases when spatial vocabulary was unavailable. Finally, there were differences between the participants with regards to the types of gesture that they used when they were unable to access language. Conclusion & Implications: The results suggest that the analysis of gesture produced by people with aphasia may provide insight into their underlying language impairment. As this was an exploratory study, with just three participants with aphasia, further research is needed.